2021
DOI: 10.17305/bjbms.2021.6488
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory cells in the ascending aortic aneurysm in patients with type 2 diabetes versus patients with hypertension

Abstract: Aortic aneurysms occur relatively frequently in the ascending thoracic aorta, but are rarely seen in patients with type 2 diabetes. Our aim was to evaluate inflammatory cell infiltration in the ascending aortic aneurysm wall in patients with diabetes without arterial hypertension (DM2 group, N=6) versus hypertensive non-diabetic patients (AH group, N=34). For histologic analysis, the sections were stained with hematoxylin-eosin and Movat pentachrome. The immunohistochemical staining was used to analyze the inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 40 publications
1
7
0
Order By: Relevance
“…In our current and recently published study [17], we observed M1 and M2 macrophages and Th, Tk, B, and plasma cells in all three wall layers in ascending thoracic aorta aneurysms in hypertensive and diabetic patients.…”
Section: Discussionsupporting
confidence: 57%
See 4 more Smart Citations
“…In our current and recently published study [17], we observed M1 and M2 macrophages and Th, Tk, B, and plasma cells in all three wall layers in ascending thoracic aorta aneurysms in hypertensive and diabetic patients.…”
Section: Discussionsupporting
confidence: 57%
“…The patients had either DM (group DM; N ═ 8) or AH (group AH; N ═ 37). The exclusion criteria were DM and AH, DM type 1, and genetic mutations [ 17 ].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations